Tests in mice of a dengue vaccine candidate made of chimeric Junin virus-like particles and conserved dengue virus envelope sequences - Mareze, Vania Aparecida (2015)
Two new vaccine candidates against dengue virus (DENV) infection were generated by fusing the coding sequences of the self-budding Z protein from Junin virus (Z-JUNV) to those of two cryptic peptides (Z/DENV-P1 and Z/DENV-P2) conserved on the envelope protein of all serotypes of DENV. The capacity of these chimeras to generate virus-like particles (VLPs) and to induce virus-neutralizing antibodies in mice was determined. First, recombinant proteins that displayed reactivity with a Z-JUNV-specific serum by immunofluorescence were detected in HEK-293 cells transfected with each of the two plasmids and VLP formation was also observed by transmission electron microscopy. Next, we determined the presence of antibodies against the envelope peptides of DENV in the sera of immunized C57BL/6 mice. Results showed that those animals that received Z/DENV-P2 DNA coding sequences followed by a boost with DENV-P2 synthetic peptides elicited significant specific antibody titers (≥6.400). Finally, DENV plaque-reduction neutralization tests (PRNT) were performed. Although no significant protective effect was observed when using sera of Z/DENV-P1-immunized animals, antibodies raised against vaccine candidate Z/DENV-P2 (diluted 1:320) were able to reduce in over 50 % the number of viral plaques generated by infectious DENV particles. This reduction was comparable to that of the 4G2 DENV-specific monoclonal cross-reactive (all serotypes) neutralizing antibody. We conclude that Z-JUNV-VLP is a valid carrier to induce antibody-mediated immune responses in mice and that Z/DENV-P2 is not only immunogenic but also protective in vitro against infection of cells with DENV, deserving further studies. On the other side, DENV´s fusion peptide-derived chimera Z/DENV-P1 did not display similar protective properties